THEORETICAL AND METHODOLOGICAL FOUNDATIONS OF THE FORMATION OF FOREIGN LANGUAGE COMMUNICATIVE COMPETENCE (Konferensiyalar | Conferences, 2024)
Professional language training adapts to modern trends, aiming to produce competitive professionals adaptable to global demands. Higher education is shifting towards globally-accredited standards, focusing on forming competencies for acquiring English communicative skills, enhancing professional potential. There's a lack of understanding on FLCC formation among future professionals in non-native English-speaking countries. Our teaching experience at foreign language universities shows students lack sufficient English proficiency for effective professional communication. This led to developing a theoretical and methodological framework for analyzing FLCC. Our aim was to design a pedagogical model with stages and technology to develop students’ motivation, FLCC readiness, communicative skills, and independent learning. It involved gradual competency building with activities to enhance perception and feedback. Its effectiveness was validated through an experiment.